Penatalaksanaan Holistik Pasien Perempuan Usia 56 Tahun dengan Ulkus Peptikum: Laporan Kasus - Tamadar Hilmi; Fitria Saftarina (Medula, 2026)
Peptic ulcer disease remains one of the most common upper gastrointestinal disorders encountered in primary healthcare settings and may lead to serious complications if not managed appropriately, including gastrointestinal bleeding, decreased quality of life, and recurrence. This case report describes a 56-year-old woman presenting with chronic epigastric pain accompanied by nausea, vomiting, abdominal fullness, and a history of gastrointestinal bleeding. Data were collected through autoanamnesis, physical examination, home visits, and medical record review. Case assessment was conducted using a holistic diagnostic approach to identify internal and external factors contributing to the patient’s condition. Internal risk factors included irregular eating habits, frequent consumption of spicy foods on an empty stomach, inadequate stress management, and limited knowledge regarding the disease and its prevention. External factors included a family healthcare-seeking pattern that remained predominantly curative and insufficient family support for health behavior modification. Interventions consisted of pharmacological therapy according to clinical indications, education regarding dietary modification and healthy lifestyle practices, stress management counseling, and family involvement in the care process. Evaluation demonstrated improvement in clinical symptoms, increased patient knowledge, and positive changes in health behavior. A   holistic, patient-centered, and community medicine approach contributed to successful management of peptic ulcer disease and prevention of recurrence in primary care settings.